Pengaruh Promosi dan Ulasan Konsumen di Platform Instagram dan Tiktok Terhadap Minat Beli - Aqidah, Ina Wadiatul; Karomatan, Tresna (Applied Business and Administration Journal, 2023)
The purpose of this research is to identify how social media marketing and user reviews on Instagram and TikTok influence consumers' propensity to make a purchase. In this quantitative study, a total of 149 participants filled out questionnaires. To examine the impact of the independent variables social media, promotions, and customer reviews on the dependent variable intent to buy multiple linear regression analytic approaches are used. The findings of the tests showed that although social media reviews had no influence on consumers' willingness to make a purchase, social media marketing had a favorable and statistically significant effect on consumers' willingness to do so.